2015
DOI: 10.4103/0019-5413.159673
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of percutaneous balloon kyphoplasty in vertebral compression fractures

Abstract: Background:Incidence of vertebral compression fractures (VCFs) is increasing due to increase in human life expectancy and prevalence of osteoporosis. Vertebroplasty had been traditional treatment for pain, but it neither attempts to restore vertebral body height nor eliminates spinal deformity and is associated with a high rate of cement leakage. Balloon kyphoplasty involves introduction of inflatable balloon into the fractured body of vertebra for elevation of the end-plates prior to fixation of the fracture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Studies show the injected pressure and the dose are positively correlated with cement extravasation rate [ 7 ]. The average injected volume in this study was 7.8 ml, which was significantly higher than the optimal reported in the literature [ 16 ]. In addition, although leaked volume accounted for only 6% of injected volume, serious neurological symptoms appeared, which may be related to spinal canal stenosis and nerve root canal stenosis of elderly patients.…”
Section: Discussionmentioning
confidence: 50%
“…Studies show the injected pressure and the dose are positively correlated with cement extravasation rate [ 7 ]. The average injected volume in this study was 7.8 ml, which was significantly higher than the optimal reported in the literature [ 16 ]. In addition, although leaked volume accounted for only 6% of injected volume, serious neurological symptoms appeared, which may be related to spinal canal stenosis and nerve root canal stenosis of elderly patients.…”
Section: Discussionmentioning
confidence: 50%
“…The VAS and the kyphotic angle were decreased obviously and lasted postoperatively, which were similar to those reported in previous literatures 19 21 . In a clinical study, Saxena et al 20 demonstrated that the VAS dropped from 6.74 preoperatively to 2.24 postoperatively, and the kyphotic angle was decreased from a preoperative mean angle of 17.41° to a postoperative mean angle of 10.59°. Foo et al 21 reported an improvement of 5.0 in VAS and a decrease of 30.77% in kyphotic angle.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale is that this approach can rapidly eliminate severe chest or back pain, allowing patients to recover normal function in a shorter time. [911] When PVP is done for VCFs, increasing amounts of bone cement have often needed to be injected into vertebrae, resulting in higher incidence of complications, including cement extravasation. [12,13] However, several studies have shown that a lower volume of bone cement could be injected while still achieving a satisfactory analgesic effect.…”
Section: Discussionmentioning
confidence: 99%